Ukrainian biaspectuality: An instantiation of compositional aspect in a verbal-aspect language - Bakardzhieva-Morikang, Svitlana; Kabakčiev, Krasimir (Lesya Ukrainka Eastern European National University, 2024)
Aspect, the perfective-imperfective contrast, is a universal phenomenon, part of man’s cognitive organization to reflect objective/subjective reality by conceptualizing referents of verbs and of nominals/NPs standing for participants in situations as temporal entities, residing in speaker-hearers’ heads and interacting between each other. Aspect is instantiated across languages through two archetypes: verbal aspect (VA) – grammatical, as in the Slavic languages, including Ukrainian; compositional aspect (CA) – complex semantico-syntactic, sporadically dependent on pragmatic discourse elements, as in English. The paper explores Ukrainian language data to, first, confirm that CA, realized mainly as a very complex interplay of sentence components, exists not only in CA languages but, albeit peripherally, also in VA languages, including Ukrainian. Second, to find out how the Ukrainian aspect is realized in sentences with biaspectual verbs and particular numbers of situation-participant NPs: three, two, one. The referents of verbs and of nominals/NPs standing for participants in situations in both VA and CA languages are part of the never-ending process of thinking and perpetual resorting to memory and are not some abstract self-contained system of symbols divorced from human cognition. Phrased otherwise, aspect, especially CA, cannot be understood within the domain of traditional grammar and mainstream linguistics with their naivist notions ignoring man’s cognitive capacity and maintaining, inter alia, that nominals/NPs are concrete/physical or abstract entities. The study of matter is ordained to physics. Linguistics must investigate not the material world but how language reflects this world and other possible (imaginable) worlds. A simple analogue is a woman in a mirror: it is not a material object but an image of a woman; likewise, a woman referred to through language is not a material object but a token of a woman. Hence, NP referents of material things are not physical entities but images of such entities, fully describable, and their kineticism is handled by verb referents, whereby the intricate CA mechanism, which is cognitive, can be observed, albeit peripherally, also in VA languages, including Ukrainian.
Keywords: compositional and verbal aspect; Ukrainian; biaspectuality; NP-V-NP mapping of (non-)boundedness